2019
DOI: 10.12669/pjms.35.5.549
|View full text |Cite
|
Sign up to set email alerts
|

Primary prophylaxis of hepatic encephalopathy in decompensated cirrhosis: Low dose vs. full dose rifaximin

Abstract: Objective: To compare efficacy of high vs low dose rifaximin for primary prophylaxis of portosystemic encephalopathy (PSE) in decompensated liver cirrhosis. Methods: In a quasi-experimental double blind randomized study at Services Institute of Medical Sciences (SIMS), Lahore from August 2017 to August 2018, patients of decompensated cirrhosis with no previous PSE were randomized to receive twice daily rifaximin 200mg in Group-A and 550mg in Group-B. Patients were followed for 6 months for development of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…All the primary and secondary outcomes from the included RCTs belonged to moderate-or highquality evidence. A recent RCT reported no significant difference between low-dose (440 mg/day) and high-dose (1,100 mg/day) rifaximin treatment (p 0.57) in primary prophylaxis of patients with HE (Sarwar et al, 2019). By contrast, the conventional therapeutic dose of rifaximin was 1,100-1,200 mg/day for HE treatment in the RCTs included herein.…”
Section: Strengths and Limitationsmentioning
confidence: 63%
“…All the primary and secondary outcomes from the included RCTs belonged to moderate-or highquality evidence. A recent RCT reported no significant difference between low-dose (440 mg/day) and high-dose (1,100 mg/day) rifaximin treatment (p 0.57) in primary prophylaxis of patients with HE (Sarwar et al, 2019). By contrast, the conventional therapeutic dose of rifaximin was 1,100-1,200 mg/day for HE treatment in the RCTs included herein.…”
Section: Strengths and Limitationsmentioning
confidence: 63%
“… Blank 6 M 6 M Pawar VB 2019 [ 38 ] India 180 Minimal HE 550 mg b.i.d. Placebo 3 M 3 M Sarwar S 2019 [ 39 ] Pakistan 75 Decompensated cirrhosis 200 mg b.i.d. ; 550 mg b.i.d.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the dosage of rifaximin, Khokhar et al found no significant difference in the efficacy of rifaximin (550 mg) once daily and twice daily (550 mg/day and 1,100 mg/ day, respectively) in the prevention of HE (29). In contrast, however, Sarwar et al reported that the rate of HE development during 6 months of follow-up was similar between a low-dose (400 mg/day) group and a full-dose group (1,100 mg/day) (30). Thus, the ideal duration and dose of rifaximin for the prevention of recurrent HE needs to be evaluated and elucidated in the near future.…”
Section: Discussionmentioning
confidence: 99%